2018
DOI: 10.1111/asj.13146
|View full text |Cite
|
Sign up to set email alerts
|

Leucine regulates slow‐twitch muscle fibers expression and mitochondrial function by Sirt1/AMPK signaling in porcine skeletal muscle satellite cells

Abstract: A previous study demonstrated that leucine upregulates the slow myosin heavy chain mRNA expression in C2C12 cells. However, the role of leucine in slow-twitch muscle fibers expression and mitochondrial function of porcine skeletal muscle satellite cells as well as its mechanism remain unclear. In this study, porcine skeletal muscle satellite cells cultured in differentiation medium were treated with 2 mM leucine for 3 days. Sirt1 inhibitor EX527, AMPK inhibitor compound C, and AMPKα1 siRNA were used to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…PGC-1α, a major regulator of mitochondrial biogenesis, is expressed in skeletal muscle (27) . Sirt1 modulates PGC-1α expression and activity (28) and plays an important role in regulating mitochondrial function (29,30) . PGC-1α and Sirt1 control mitochondrial biogenesis and function via the induction and activation of several downstream nuclear transcription factors, such as NRF1, mitochondria transcription factor B1 (TFB1M), ATP5G and cytochrome c (Cytc) (6,29,31) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGC-1α, a major regulator of mitochondrial biogenesis, is expressed in skeletal muscle (27) . Sirt1 modulates PGC-1α expression and activity (28) and plays an important role in regulating mitochondrial function (29,30) . PGC-1α and Sirt1 control mitochondrial biogenesis and function via the induction and activation of several downstream nuclear transcription factors, such as NRF1, mitochondria transcription factor B1 (TFB1M), ATP5G and cytochrome c (Cytc) (6,29,31) .…”
Section: Discussionmentioning
confidence: 99%
“…Type I (slow-twitch) muscle fibres are rich in the mitochondria (3,32) . It has been reported that some nutrients (such as leucine and resveratrol) can regulate type I (slowtwitch) muscle fibres expression by improving the mitochondrial biogenesis and function (29,30,33) . In the present study, our data found that dietary supplementation of 1•0 % Arg significantly increased the PGC-1α, Sirt1 and Cytc protein expressions, the PGC-1α, NRF1, TFB1M, Cytc and ATP5G mRNA expressions and the mtDNA content, suggesting that Arg plays an important role in regulating mitochondrial biogenesis and function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both BCAA mixture and leucine could increase the mitochondrial content and induce the expression of TFAM and mitochondrial component genes. However, several studies have shown that valine did not affect the mitochondrial biogenesis ( 49 , 51 , 52 ).…”
Section: Bcaas and Fatty Acids Regulate Mitochondrial Functionmentioning
confidence: 99%
“…These results suggest that in skeletal muscle, leucine-induced PGC-1α expression depends on mTORC1 but a feedback loop involving mTORC1 and PGC-1α may also exist. Interestingly, piglet primary muscle cells treated with leucine for 3 days increased PGC-1α protein and mRNA (and promoted slow myosin heavy chain phenotype) yet was dependent on SIRT1 and AMPKα [ 61 ]. Similarly, C2C12 myotubes treated with leucine for 24 or 48 h also required SIRT1 and AMPKα to increase PGC-1α mRNA [ 55 ].…”
Section: Potential Nutritional Therapiesmentioning
confidence: 99%